Bone : Rock Jaw, Master of the Eastern Border / 5. - Smith, Jeff, 1960 February 27- (Bone, 2007)
While trying to return a lost ratlike cub to its home in the mountains, Fone and Smiley Bone encounter Rock Jaw, the wicked master of the eastern border. Presented in graphic novel format.